Peer learning: mentoring in a Portuguese as a foreign language course - Estrela, Antónia (2022)
Mentoring is valued in foreign language learning, as it is based on the recognition of the benefits of the interaction between peers. This paper aims at presenting the results of a mentorship experience thought for a Portuguese as a Foreign Language course in higher education, in 2017/18. The mentees are Erasmus students attending these courses. This initiative was developed through the preparation of mentors, structured sessions of interaction between mentors and mentees, a reflection upon the experienced process and the administration of questionnaires to the participants. Data were collected through direct observation, following a naturalist observation protocol. There was a content analysis of the answers for open questions and a statistical analysis of all answers. Results suggest the existence of positive effects of the mentoring program, such as the individual, social and linguistic development of the mentors, the mentees’ integration and learning of Portuguese and the interpersonal relationship in both groups.